ANALSISIS KEBERHASILAN LITERASI DA NUMERASI SISWA SEKOLAH DASAR PADA PROGRAM KAMPUS MENGAJAR ANGKATAN 5 DI KABUPATEN MAJALENGKA MENGGUNAKAN METODE NAÃVE BAYES - Dede Abdurahman; Tri Ferga Prasetyo; Iid Muiz Awaludin (Universitas Alma Ata, 2024)
The teaching campus provides collaboration between students and teachers in the development of learning which has an impact on strengthening literacy and numeracy. Results of the Program for International Student Assessment (PISA) and Trends in International Mathematics and Science Study (TIMSS) in 2015 Indonesia obtained a literacy score of 397 and a numeration of 386 ranked 62 out of 72 countries while in 2018 Indonesia obtained a literacy score of 371 and a numeration of 379 ranked 74 out of 79 countries. In Indonesia, parents pay little attention to their children's literacy and numeracy skills, so that the literacy and numeracy skills of students in Indonesia are relatively low. With the presence of teaching campus students it is hoped that they can become partners of teachers in developing literacy and numeracy learning models. To see the results of the success rate of teaching campus students in applying literacy and numeracy learning models, an analysis using the classification method is needed. Therefore, the authors make an analysis of the literacy and numeracy success of elementary school students in the class 5 teaching campus program using the NaÃ¯ve Bayes Classifier method. Data classification techniques were carried out manually and by using the Rapidminer software, data classification was carried out by dividing into two categories in the form of literacy and numeracy results. The results of testing the training data and data testing for literacy get an accuracy value of 95.71%, 97.92% precision, 95.92% recall while for numeration get an accuracy value of 95.71%, 93.75% precision, 96.77% recall.